ASSESSMENT OF CORROSION RESISTANT ALLOY (CRA) CLAD MATERIAL FOR GEOTHERMAL WELLHEAD PIPING SYSTEM (ASEAN Engineering Journal, 2022)
The geothermal power industry has reported a wide range of corrosion problems. Given the extremely corrosive conditions to be treated in the geothermal sector and the benefits of reduced unplanned downtime when used, operating cost savings would be expected if more CRAs clad products were used. The selection of suitable Corrosion Resistant Alloy (CRA) material is vital for plant operability, especially in challenging well conditions with low pH value and carbon dioxide, hydrogen sulphide, and hydrogen chloride content. The primary examined material alloy 625 given its exceptional erosion and corrosion resistance. Alloy 625 was selected based on a preliminary material selection review of its mechanical and chemical properties to withstand a corrosive environment. The study method emphasizes selected material from dissimilar alloying steel grades (e.g. Backing Steel + CRA material) based on its mechanical properties, chemical composition, macro and micro examination, and corrosion resistance using the common industrial standards. The study focuses on using Alloy 625 cladding using the overlay method to determine the weld overlay's suitability for the geothermal production system. The weld overlay cladding is performed to increase the components' life and as a replacement using an expensive corrosion resistant solid material. In many cases, only the surface of the material requires corrosion resistance and carbon or alloy steel can be clad with a more corrosion-resistant alloy. Up to 50% of the cost of using the solid alloy can be saved by cladding. This study also describes the technical and economic advantages of using Alloy 625 clad material in the present condition